Sustainable Synthesis of Bacterial Cellulose Nanocrystals from Glucomannan-Based Bacterial Cellulose - Widjaja, Tri; Nurkhamidah, Siti; Ni’mah, Hikmatun; Wardhono, Endarto Yudo; Rohmah, Aisyah Alifatul Zahidah; Tirta, Anggi; Nailah, Rossesari; Sari, Citra Yulia (Universitas Gadjah Mada, 2025)
Bacterial cellulose (BC), derived from glucose fermentation, is a renewable material known for its abundant availability, quick production, cost-effectiveness, and eco-friendly characteristics. This study focuses on converting BC into BC nanocrystals (BCNC) via fermentation, hydrolysis using acid solutions, and ultrasonication. Glucomannan flour with concentrations of 50, 60, and 90% was fermented using Acetobacter xylinum for 10 days at pH 5 to produce BC. The BC was then hydrolyzed with HCl solutions at 1, 2, 3, 4, and 5 M concentrations, followed by sonication. The 90% glucomannan flour yielded the highest BC amount (22.61 g). BCNC hydrolyzed with 1 M HCl exhibited the highest crystallinity (86%) and an elongated rod-like morphology. In contrast, hydrolysis with 4 and 5 M HCl caused carbonization, reducing crystallinity to below 30%. Particle size analysis showed the largest particle size for BCNC-2 (549.4 nm) and the smallest for BCNC-5 (207.2 nm). This research highlights the potential of glucomannan as a resource to produce BCNC for sustainable materials for various applications.